Nematic topological defects positionally controlled by geometry and external fields - Kurioz, Pavlo; Kralj, Marko; Murray, Bryce S.; Rosenblatt, Charles; Kralj, Samo (Beilstein Journal of Nanotechnology, 2018)
Using a Landau–de Gennes approach, we study the impact of confinement topology, geometry and external fields on the spatial positioning of nematic topological defects (TDs). In quasi two-dimensional systems we demonstrate that a confinement-enforced total topological charge of m > 1/2 decays into elementary TDs bearing a charge of m = 1/2. These assemble close to the bounding substrate to enable essentially bulk-like uniform nematic ordering in the central part of a system. This effect is reminiscent of the Faraday cavity phenomenon in electrostatics. We observe that in certain confinement geometries, varying the correlation length size of the order parameter could trigger a global rotation of an assembly of TDs. Finally, we show that an external electric field could be used to drag the boojum fingertip towards the interior of the confinement cell. Assemblies of TDs could be exploited as traps for appropriate nanoparticles, opening several opportunities for the development of functional nanodevices.
Keywords: nanoparticles; nematic liquid crystals; topological charge; topological defects

(untitled) - Mermin, N. D. (Rev. Mod. Phys., 1979)

(untitled) - Zurek, W. H. (Nature, 1985)

(untitled) - Hobson, A. (Am. J. Phys., 2013)

(untitled) - Skyrme, T. H. R. (Nucl. Phys., 1962)

Soft Matter Physics - Kleman, M.; Lavrentovich, O. D. (Springer, 2003)

(untitled) - Kurik, M. V.; Lavrentovich, O. D. (Sov. Phys. - Usp., 1988)

(untitled) - Kikuchi, H.; Yokota, M.; Hisakado, M.; Yang, H.; Kajiyama, T. (Nat. Mater., 2002)

(untitled) - Karatairi, E.; Rožič, B.; Kutnjak, Z.; Tzitzios, V.; Nounesis, G.; Cordoyiannis, G.; Thoen, J.; Glorieux, C.; Kralj, S. (Phys. Rev. E, 2010)

(untitled) - Coursault, D.; Grand, J.; Zappone, B.; Ayeb, H.; Levi, G.; Felidj, N.; Lacaze, E. (Adv. Mater., 2012)

(untitled) - Palffy-Muhoray, P. (Phys. Today, 2007)

(untitled) - Rožič, B.; Tzitzios, V.; Karatairi, E.; Tkalec, U.; Nounesis, G.; Kutnjak, Z.; Cordoyiannis, G.; Rosso, R.; Virga, E. G.; Muševič, I.; Kralj, S. (Eur. Phys. J. E, 2011)

(untitled) - Cordoyiannis, G.; Jampani, V. S. R.; Kralj, S.; Dhara, S.; Tzitzios, V.; Basina, G.; Nounesis, G.; Kutnjak, Z.; Tripathi, C. S. P.; Losada-Pérez, P.; Jesenek, D.; Glorieux, C.; et al. (Soft Matter, 2013)

(untitled) - Ok, J. M.; Kim, Y. H.; Lee, T. Y.; Yoo, H.-W.; Kwon, K.; Jung, W.-B.; Kim, S.-H.; Jung, H.-T. (Langmuir, 2016)

(untitled) - Kaiser, P.; Wiese, W.; Hess, S. (J. Non-Equilib. Thermodyn., 1992)

(untitled) - Kralj, S.; Virga, E. G. (J. Phys. A: Math. Gen., 2001)

(untitled) - Nobili, M.; Durand, G. (Phys. Rev. A, 1992)

(untitled) - Murray, B. S.; Pelcovits, R. A.; Rosenblatt, C. (Phys. Rev. E, 2014)

(untitled) - Kralj, S.; Murray, B. S.; Rosenblatt, C. (Phys. Rev. E, 2017)

(untitled) - Kralj, S.; Rosso, R.; Virga, E. G. (Phys. Rev. E, 2008)

(untitled) - Volovik, G. E. (JETP Lett., 1978)